Safeguarding Participants in Psychiatric Genetic Research: Perspectives of Key Stakeholder Groups. Issue 6 (19th November 2019) - Rostami, Maryam; Dunn, Laura B.; Kim, Jane Paik; Roberts, Laura Weiss
ABSTRACT: Public trust in research depends on implementation of research protections. Genetic and psychiatric research may elicit "exceptionalism, " the belief that these types of research deserve special protections. Genetic information has been viewed as different from other health information. Psychiatric research has been scrutinized based on concerns about the impact of psychiatric illness on individuals' abilities to make decisions. This study compared four stakeholder groups' attitudes toward research safeguards. Psychiatric genetic researchers and institutional review board chairs received structured surveys. Individuals with mental illness and family members participated in semistructured interviews. Paired sample t‐tests were used to compare mean ratings of importance of safeguard procedures for genetic versus nongenetic research on physical versus mental illnesses. All groups provided higher ratings for the importance of safeguards for genetic research and for mental illness. Individuals with mental illness and family members rated the importance of safeguards more highly than researchers and chairs did. Results of generalized linear models showed significant effects of gender and ethnicity.